A Comprehensive Analysis of Key Immune Checkpoint Receptors on Tumor-Infiltrating T Cells From Multiple Types of Cancer - Li, Xi; Wang, Rouzheng; Fan, Peiwen; Yao, Xuan; Qin, Ling; Peng, Yanchun; Ma, Miaomiao; Asley, Neil; Chang, Xuimei; Feng, Yaning; Hu, Yunhui; Zhang, Yonghong; et al. (Frontiers in Oncology, 2019)
Background: Cancer patients often display dysfunctional anti-tumor T cell responses. Since noteworthy benefits of immune checkpoint pathway blockade, such as PD-1 inhibitors, have been achieved in multiple advanced cancers, the next critical question is which mono- or combinatorial blockade regimens may reinvigorate anti-tumor T cell immunity in those cancer patients while limiting immune-related adverse effects. Method: This study recruited, in total, 172 primary cancer patients (131 were blood-tumor matched patients) who were treatment-naïve prior to the surgeries or biopsies, covering the 8 most prevalent types of cancer. With access to fresh surgical samples, this study simultaneously investigated the ex vivo expression level of 8 known immune checkpoint receptors (PD-1, CTLA-4, Tim-3, 2B4, KLRG-1, TIGIT, BTLA and CD160) on tumor infiltrating T cells (TILs) and paired circulating T cells in blood from a 131-patient cohort. Results: We found increased expression of PD-1 and Tim-3 but decreased expression of BTLA on tumor-infiltrating T cells when compared to peripheral blood from multiple types of cancer. Moreover, our co-expression analysis of key immune checkpoint receptors delineates “shared” subsets as PD-1+Tim-3+TIGIT+2B4+KLRG-1-CTLA-4- and PD-1+TIGIT+2B4+Tim-3-KLRG-1-CTLA-4-, from bulk CD8 TILs. Furthermore, we found higher frequency of advanced differentiation stage T cells (CD27-CCR7-CD45RA-) amongst the “shared” subset (PD-1+Tim-3+TIGIT+2B4+KLRG-1-CTLA-4-) in bulk CD8 TILs was associated with poorly differentiated cancer type in cervical cancer patients. Conclusions: To our knowledge, our study is the first comprehensive analysis of key immune checkpoint receptors on T cells in treatment-naïve, primary cancer patients from the 8 most prevalent types of cancer. These findings might provide useful information for future design of mono-/combinatorial blockades and/or genetically-modified T cell immunotherapy.